Environmental Education Berbasis Konsep Islam dalam Mereduksi Aktivitas Kerusakan Ekologis di Kec. Hutabargot Kab. Mandailing Natal - Paisal Rahmat; Marlian Arif Nasution; Zuhdi Zuhdi; Muhammad Irsan Barus (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The PKM STAIN Mandailing Natal team carried out a workshop with the theme “Environmental Education Based on Islamic Concepts in Reducing Ecological Damage Activities in Kec. Hutabargot Kab. Mandailing Natal". This workshop activity aims to provide education to the community regarding good environmental management according to Islamic concepts. The idea of implementing this workshop activity refers to the problem of low ethics and public understanding in managing the environment, excessive exploitation of nature through illegal gold mining activities so that the environment is polluted and low attention to environmental hygiene. The method used in this service is the Participatory Action Research (PAR) method, which is in the form of a workshop to socialize Environmental Education through a community movement that cares about the environment to strengthen public understanding in managing the environment. Based on the evaluation of activities, the results obtained, first, the formation of cooperation between the environmental service and the district government. Hutabargot to form a waste bank management team; second, the establishment of an environmental care movement in every village to promote the importance of a healthy and clean environment; third, the creation of cooperation with religious leaders in each village to include environmental education materials in their da'wah activities as an effort to educate the community in a sustainable manner.